Call It Courage - Sperry, Armstrong 1897- (New York : Macmillan, 1940)
A legend of a Polynesian boy, who, called a coward for being afraid of the sea, sets out to overcome his fears.
Keywords: Legends -- Polynesia; Courage -- Folklore; Polynesia -- Folklore